Decision-Making Behaviour Evolution Among Pork Supply and Demand Subjects Under Normalisation of COVID-19 Prevention and Control: A Case Study in China - Ma, Li; Wang, Yidi; Teng, Yun (Frontiers in Public Health, 2022)
Affected by the COVID-19, there were short-term uncertainties in China’s live pig industry supply chain. Due to the insufficient supply of pork, the price of pork rose from 33.21 yuan/kg at the end of 2019 to 37.46 yuan/kg in mid-February and fell to 26.41 yuan/kg in mid-May. To restore pig supply and stabilize prices, China issued relevant policies. In view of the current effective control of COVID-19 in China, this paper constructed an evolutionary game model of China’s pork supply and demand stakeholders under normalization of COVID-19 prevention and control, analysed the behavioural strategies of consumers, government and pig farmers,, used MATLAB software for data simulation, and expounded on the evolution path and the characteristic rule of tripartite decision-making behaviours. The results showed that government supervision costs, evaluation of government by consumers and pig farmers, government subsidies to pig farmers and consumers, and the proportion of stakeholder behaviours affected the formation of tripartite relationships. The results provide a useful reference for the government to formulate effective policies, increase pig supply, and stabilize pork prices.